The Role of Mass Media and Healthy Lifestyle Changes in the Digital Era - Hutapea, Amelia Caroline; Hidayat, Taufik Wal (EDUCTUM: Journal Research, 2025)
This study aims to examine the role of mass media in shaping adolescents' perceptions of a healthy lifestyle. The research method used a qualitative literature study approach, analyzing various scientific sources, media articles, research reports, and relevant digital publications. The results of the study indicate that mass media, particularly digital media, plays a significant role in conveying health messages to adolescents through engaging, persuasive, and easily accessible content. Adolescent communication patterns have shifted from face-to-face communication to faster, more visual, interactive, and participatory digital communication. Furthermore, the presence of influencers on social media is a crucial factor in the integration of health messages, acting as a source of inspiration while also potentially disseminating inaccurate information. These findings emphasize the importance of strong media literacy in adolescents so they can critically filter information, choose appropriate healthy behaviors, and build a healthy lifestyle independently and responsibly.